DIPG-32. AKT SIGNALING DRIVES RESISTANCE TO ONC201 IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (4th December 2020) - Jackson, Evangeline R; Duchatel, Ryan J; Mannan, Abdul; Hulleman, Esther; Carcaboso, Angel M; Monje, Michelle; McCowage, Geoff B; Alvaro, Frank; Dun, Matthew D
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive, childhood brainstem cancer with a median overall survival of 10 months post diagnosis. Remarkably, 80–90% of patients harbor recurring point mutation in histone H3, which induces a lysine for methionine substitution at amino acid 27 (H3K27M) in either H3.1 ( HIST1H3B 25%) or H3.3 ( H3F3A 65%) variants. Using the blood-brain barrier (BBB) permeable DRD2 antagonist, ONC201 (in clinical trials for DIPG and H3K27M-mutant gliomas – NCT03416530), we hypothesized that DRD2 antagonism would induce TRAIL expression via indirect inhibition of AKT and ERK signaling, to drive apoptosis in both H3.1K27M and H3.3K27M patient-derived DIPG cell lines alike. For the first time, we reveal that ONC201 shows efficacy in 100% of WT-H3 and H3.1K27M mutant DIPG cell lines (n=5), compared to 50% of H3.3K27M mutant DIPGs (n=6). Investigations to identify the mechanisms of resistance to ONC201, revealed that cell lines with decreased sensitivity upregulated the PI3K/AKT/MTOR signaling axis to drive phosphorylation of AKT and increase metabolic activity. Combined administration of ONC201 and the BBB-permeable PI3K/AKT inhibitor, paxalisib (previously GDC-0084, in clinical trials for newly diagnosed DIPG – NCT03696355), showed synergistic cytotoxicity, reduced PI3K/AKT signaling and metabolic reprogramming to drive apoptosis in all DIPG cell lines tested. This combination was used to treat a 3-year-old DIPG patient, commencing 14 weeks post disease progression, completing 40 weeks of therapy prior to her passing, December 2019. These studies highlight the potential of combined administration of two safe, BBB penetrant, oral targeted therapies and supports testing under clinical trial conditions.